NILAI DASAR PENDIDIKAN ISLAM DALAM FALSAFAH PODA NA LIMA - Wahyu Parondingan Siregar (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
The Angkola-Mandailing have long known the philosophy of life of Poda Na Lima as an ancestral heritage whose practice is highly respected. Poda Na Lima is advice that teaches about the importance of maintaining cleanliness such as cleaning the heart, cleaning the body, cleaning clothes, cleaning the house, and cleaning the yard. Character education is an effort made in fostering, shaping, and improving the character of children and students. In character education, there are 18 values such as religious values, honesty, tolerance, discipline, hard work, independence, creativity, and others. This study aims to see and analyze the values of character education in the Poda Na Lima philosophy where there are five values: religious values, honest values, environmental care values, social care values, and responsibility values. This study used a qualitative research method with the type of library research, namely viewing and reading books, journals, and theses as references in this research. This is certainly in line with the Poda Na Lima philoshopy which gives a signal to cleanse the heart as the first step. Thus in the Poda Na Lima Philoshopy there are basic values of Islamic are in line with the goals of national education namely the existence of a generation that has the ability and quality character to face the challenges of changing times.